The Nexus Between International Marketing Research and Innovation Capacity: Evidence from Turkish Exporters (European Journal of Marketing and Economics, 2026)
A firm's ability to innovate is a cornerstone of sustained competitive advantage, but the mechanisms that drive this capacity are not uniformly understood, particularly in the context of international business. While internal factors like R&D investment and organizational culture are well-documented, the specific role of external market engagement remains underexplored. This study addresses that gap by examining the critical nexus between international marketing research and innovation capacity among Turkish firms that are active exporters. We argue that robust and systematic international marketing research serves as a prerequisite for leveraging global market opportunities to foster innovation, moving beyond a firm's established domestic routines. Using a qualitative research approach, we conducted in-depth interviews with key decision-makers and founders from a sample of exporters who are members of the Aegean Export Union in Izmir, Turkey. This methodology allowed for a nuanced exploration of the processes through which market intelligence gathered abroad directly influences a firm's capacity for product and process innovation. The findings reveal a multi-faceted process where international market insights lead to the identification of new customer needs and technological trends, which in turn stimulates internal innovation efforts. This research offers significant contributions by illuminating the dynamic interplay between a firm's market orientation in a global context and its ability to innovate, providing a detailed understanding of a key driver of competitive advantage for firms in emerging economies.
Keywords: International Marketing Research, Innovation Capacity, Exporting, Market Orientation, Qualitative Research, Turkish Firms